2020
DOI: 10.1186/s12884-020-03372-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous endometrial volumetric analysis for endometrial receptivity assessment on assisted reproductive technology cycles

Abstract: Background Human implantation is a complex process requiring synchrony between a healthy embryo and a functionally competent or receptive endometrium. In order to assess endometrial receptivity in Assisted Reproductive Technology (ART) cycles serial evaluation of endometrial volumetric analysis may have a predictive value on a positive outcome. Methods Serial 3D transvaginal ultrasound performed in women on ART cycle to evaluate embryo implantation predictors. Prospective case control study of 169 subjects w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our results showed that endometrial volume differed between the two groups in the univariate analysis but not in the multivariate analysis, suggesting that the endometrial volume was not an independent predictor of pregnancy. Our study showed that endometrial morphology was not a factor associated with pregnancy occurrence ( P > 0.05), consistent with the results of Martins et al [ 3 ]. Uterine artery parameters (mPI, mRI, and mSD) were not significantly correlated with pregnancy occurrence (P > 0.05), which might be because the uterine artery supplies several vital structures, such as fallopian tubes and ovaries, in addition to the uterus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that endometrial volume differed between the two groups in the univariate analysis but not in the multivariate analysis, suggesting that the endometrial volume was not an independent predictor of pregnancy. Our study showed that endometrial morphology was not a factor associated with pregnancy occurrence ( P > 0.05), consistent with the results of Martins et al [ 3 ]. Uterine artery parameters (mPI, mRI, and mSD) were not significantly correlated with pregnancy occurrence (P > 0.05), which might be because the uterine artery supplies several vital structures, such as fallopian tubes and ovaries, in addition to the uterus.…”
Section: Discussionsupporting
confidence: 93%
“…The success of an IVF-ET depends on certain factors, including endometrial receptivity. Endometrial receptivity refers to the window of implantation (WOI) during which the uterus allows embryo implantation to occur [ 2 ] and is considered one of the most important factors [ 3 ]. A satisfactory endometrial receptivity refers to the state in which the endometrium allows the embryo to adhere, with subsequent corresponding endometrial changes for the implantation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Embryo implantation success depends mainly on two conditions: the degree of embryo development and endometrial receptivity (ER). ER refers to the ability of the endometrium to allow the embryo to contact, localize, adhere, and implant at a specific time, referred to as the window of implantation (WOI) ( 1 ). The WOI, usually days 20–24 of the normal menstrual cycle or days 7–10 of the LH peak, is when the embryo is most likely to implant.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on the effects of independent ultrasound parameters on embryo implantation, including endometrial patterns and thickness, which have been repeatedly tested and compared with pregnancy rates during in vitro fertilization (IVF) cycles with conflicting results [2,3]. In recent years, some studies have focused on the comprehensive evaluation of ultrasound parameters for predicting endometrial receptivity, including conservative endometrial measurements, endometrial myometrial junction studies, and comprehensive scores of endometrial and subendometrial Doppler indices [4,5], which are considered to represent better the actual ability of the endometrium to accept embryos.…”
Section: Introductionmentioning
confidence: 99%